Essence of Crime - Tulyakov V. A.; Tuliakov, Viacheslav; Туляков, Вячеслав Олексійович; Tuliakov, Viacheslav O.; Tuliakov, Viacheslav O. (My University, 2020)
The lecture of cource "Crininal Law (General Part)" for students of National University "Odessa Law Academy".
video lecture
Tuliakov V. Essence of Crime : video lecture / V. Tuliakov. - Odessa, 2020. - Access mode: https://youtu.be/rI-ZmdsM04M
Keywords: кримінальне право; уголовное право; criminal law; crime; essence of crime